Why do firms engage in selective hedging? - Tim R. Adam; Chitru S. Fernando; Jesus M. Salas (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
Surveys of corporate risk management document that selective hedging, where managers incorporate their market views into firms' hedging programs, is widespread in the U.S. and other countries. Stulz (1996) argues that selective hedging could enhance the value of firms that possess an information advantage relative to the market and have the financial strength to withstand the additional risk from market timing. We study the practice of selective hedging in a 10-year sample of North American gold mining firms and find that selective hedging is most prevalent among firms that are least likely to meet these valuemaximizing criteria - (a) smaller firms, i.e., firms that are least likely to have private information about future gold prices; and (b) firms that are closest to financial distress. The latter finding provides support for the alternative possibility suggested by Stulz that selective hedging may also be driven by asset substitution motives. We detect weak relationships between selective hedging and some corporate governance measures, especially board size, but find no evidence of a link between selective hedging and managerial compensation.
Keywords: G11; G14; G32; G39; 330; corporate risk management; selective hedging; speculation; financial distress; corporate governance; managerial compensation; Goldbergbau; Risikomanagement; Hedging; Spekulation; Corporate Governance; Managervergütung; Schätzung; USA